MEKANISME TATA KELOLA DAN PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE - Carin Jimantoro; Kesya Agnes Maria; Dyna Rachmawati (Jurnal Riset Akuntansi dan Keuangan, 2023)
ABSTRACT This study aims to examine the effect of governance mechanisms on ESG disclosure. Internal and external components make up governance mechanisms. The internal governance mechanism is the board of directors, while the external mechanism is the audit committee and institutional ownership. This study uses a publicly traded manufacturing company with an observation period of 2016–2020. The hypothesis testing tool is multiple regression analysis. The results of testing 361 pieces of cross-sectional data show that, first, board of director characteristics, as measured by board size and number of board meetings, have a positive effect on ESG disclosure. Second, the characteristics of the audit committee, which include size, independence, number of meetings, and financial expertise, have no effect on ESG disclosures. Third, institutional ownership has a positive effect on ESG disclosure. Fourth, the control variables, namely profitability and company size, have a positive effect on ESG disclosure. Thus, the role of the board of directors as an internal mechanism and institutional ownership as an external mechanism is greater than that of the audit committee in enforcing the implementation of governance so as to be able to encourage ESG disclosure. Keywords: Internal governance mechanism, external governance mechanism, ESG disclosure. ABSTRAK Penelitian ini bertujuan untuk menguji pengaruh mekanisme tata kelola terhadap pengungkapan ESG. Mekanisme tata kelola terdiri dari internal dan eksternal. Mekanisme tata kelola internal adalah dewan direksi, sedangkan mekanisme eksternal adalah komite audit dan kepemilikan institusional. Penelitian ini menggunakan perusahaan manufaktur terbuka dengan periode pengamatan 2016 – 2020. Alat uji hipotesis adalah analisis regresi majemuk. Hasil pengujian 361 data cross section membuktikan bahwa pertama, karakteristik dewan direksi yang diukur dengan ukuran dewan direksi dan jumlah rapat dewan direksi berpengaruh positif terhadap pengungkapan ESG. Kedua, karakteristik komite audit yang meliputi ukuran, independensi, jumlah rapat, dan keahlian keuangan tidak berpengaruh terhadap pengungkapan ESG. Ketiga, kepemilikan institusional berpengaruh positif terhadap pengungkapan ESG. Keempat, variabel kontrol yaitu profitabilitas dan ukuran perusahaan berpengaruh positif terhadap pengungkapan ESG. Dengan demikian, peranan dewan direksi sebagai mekanisme internal, dan kepemilikan institusional sebagai mekanisme eksternal lebih besar dibandingkan komite audit dalam menegakkan pelaksanaan tata kelola sehingga mampu mendorong pengungkapan ESG. Kata kunci: Mekanisme tata kelola internal, mekanisme tata kelola eksternal, pengungkapan ESG